PENYULUHAN SANITASI KOMUNAL DI DESA TAMBAK BARU KECAMATAN MARTAPURA KOTA KABUPATEN BANJAR - Eka Purnamasari; Akhmad Gazali; Robiatul Adawiyah (Universitas Islam kalimantan MAB, 2017)
Tambak Baru is one of 25 villages. Village located in the District Martapura Banjar district. The majority of the population are farmers Tambak Baru (peasant) and household handicraft industry and artisan labor. Geographically, the new Village Pond located at coordinates between 3.23594 ° S and 114 ° 35'30